2000
DOI: 10.1523/jneurosci.20-18-06743.2000
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Somatodendritic GABAA Receptor Channels in Rat Hippocampal Neurons: Evidence for a Role of the Small GTPase Rac1

Abstract: The role of the cytoskeleton in the activity of GABA(A) receptors was investigated in cultured hippocampal neurons. Receptor currents were measured with the whole-cell patch-clamp technique during repetitive stimulation with 1 microm muscimol. After destruction of the microtubular system with nocodazol, muscimol-induced currents showed a rundown by 78%. A similar rundown was observed when actin fibers were destroyed with latrunculin B or C2 toxin of Clostridium botulinum. Because the small GTPases of the Rho f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 69 publications
7
44
0
Order By: Relevance
“…This result suggests that Ral A, filamin A, and HCN1 are strictly packed in a macromolecular complex. It is also interesting to note that monomeric G-proteins of the Rho family, of which Ral A is a member, are involved in the modulation of ionic channels such as N-methyl-D-aspartate and ␥-aminobutyric acid type A receptors (38,39). We found that the interaction between HCN1 and filamin A is conserved in in vivo conditions as shown by co-immunoprecipitation of the two proteins from bovine brain (Fig.…”
Section: Resultssupporting
confidence: 51%
“…This result suggests that Ral A, filamin A, and HCN1 are strictly packed in a macromolecular complex. It is also interesting to note that monomeric G-proteins of the Rho family, of which Ral A is a member, are involved in the modulation of ionic channels such as N-methyl-D-aspartate and ␥-aminobutyric acid type A receptors (38,39). We found that the interaction between HCN1 and filamin A is conserved in in vivo conditions as shown by co-immunoprecipitation of the two proteins from bovine brain (Fig.…”
Section: Resultssupporting
confidence: 51%
“…Furthermore, microtubules (van Zundert et al, 2002(van Zundert et al, , 2004 and F-actin disruptions alter GlyR stabilization at synapses, indicating that the cytoskeleton controls the number of inhibitory receptors at synapses. However, the number of synaptic GABA A R clusters is not modified in these conditions (Allison et al, 1998(Allison et al, , 2000 (but see Meyer et al, 2000;Petrini et al, 2003). It should be noted that cell types and quantification methods used in these studies differ.…”
Section: Discussionmentioning
confidence: 90%
“…Many of the filopodia-like protrusions induced by PAK3 dominant-negative mutation were devoid of postsynaptic densities or expressed only very small PSDs and/or lacked presynaptic partners. It is interesting in this respect that Rac1 signaling has also been implicated in receptor aggregation at inhibitory interneurons (Meyer et al, 2000) and that reduced kalirin expression was associated with a redistribution of PSD markers, as well as elimination of presynaptic endings (Ma et al, 2003). Furthermore, in Drosophila, PIX mutation is associated with defects in the stabilization of postsynaptic structures, an effect that involves a PAK homolog (Parnas et al, 2001).…”
Section: Discussionmentioning
confidence: 99%